Initial findings on the Boor language - James Roberts (Afrika und Übersee, 2021)
This article provides the first published information on Boor, an Eastern Chadic language spoken in a single village in the Moyen Chari Region of Chad. First, the sociolinguistic situation of the language and its speakers is presented, along with the conditions under which the present data was collected. Then follows a very provisional statement about the consonant and vowel systems of the language, along with some remarks about nominal and verbal morphology. The article finishes by presenting several tables of lexical data, comparing Boor words with those of several nearby languages, in the interest of better understanding the place of Boor within the Eastern Chadic family.